Searching for criteria in evaluating the monofin swimming turn from the perspective of coaching and improving technique - Rejman, M.; Borowska, G. (Journal of Sports Science & Medicine, 2008)
This study aims to analysise the selected kinematic parameters of the monofin swimming turn. The high complexity of performing turns is hindered by the large surface of the monofin, which disturbs control and sense of the body in water. A lack of objective data available on monofin swimming turns has resulted in field research connected with the specification of parameters needed for the evaluation of the technique. Therefore, turns observed in elite swimmers contain underlying conclusions for objective criteria, ensuring the highest level of coaching and the improving of turns in young swimmers. Six, high level, male swimmers participated in the study. The subject of the analysis was the fastest turn, from one out of three trial turns made after swimming a distance of 25 m. Images of the turns were collected from two cameras located under water in accordance with the procedures of the previous analyses of freestyle turns. The images were digitized and analysed by the SIMI®- Movement Analysis System. The interdependency of the total turn time and the remaining recorded parameters, constituted the basis for analysis of the kinematic parameters of five turn phases. The interdependency was measured using r- Pearson's correlation coefficients. The novel character of the subject covered in this study, forced interpretation of the results on the basis of turn analyses in freestyle swimming. The results allow for the creation of a diagram outlinig area of search for an effective and efficient monofin swimming turn mechanism. The activities performed from the moment of wall contact until the commencement of stroking seem to be crucial for turn improvement. A strong belief has resulted that, the correct monofin swimming turn, is more than just a simple consequence of the fastest performance of all its components. The most important criteria in evaluating the quality of the monofin swimming turn are: striving for the optimal extension of wall contact time, push-off time and glide time.